Search for a heavy top-quark partner in final states with two leptons with the ATLAS detector at the LHC - Anduaga, Xabier Sebastián (2012)
The results of a search for direct pair production of heavy top-quark partners in 4.7 fb-1 of integrated luminosity from pp collisions at √s = 7 TeV collected by the ATLAS detector at the LHC are reported. Heavy top-quark partners decaying into a top quark and a neutral non-interacting particle are searched for in events with two leptons in the final state. No excess above the Standard Model expectation is observed. Limits are placed on the mass of a supersymmetric scalar top and of a spin-1/2 top-quark partner. A spin-1/2 top-quark partner with a mass between 300 GeV and 480 GeV, decaying to a top quark and a neutral non-interacting particle lighter than 100 GeV, is excluded at 95% con dence level.